Two new species of apterous endemic ground beetle genus Omphra Dejean (Carabidae: Anthiinae: Helluoniini) from India. (2nd January 2022) - Sv, Akhil; Sabu, Thomas K.
ABSTRACT: Two new species of apterous endemic ground beetle Omphra Dejean, 1825, O. balli sp. nov . from the semi-arid region in Central India and O. erwini sp. nov . from the semi-arid region in Northwestern India are described. Modified key to the species is given. The nine known species of the genus Omphra are divided into three groups ( Pilosa group, Complanata group and Atrata group) based on the morphological traits and biogeographical distribution. Omphra ballihttp://www.zoobank.org/urn:lsid:zoobank.org:act:DDD549F3-C159-4C02-BCE4-EE7D459487CC Omphra erwinihttp://www.zoobank.org/urn:lsid:zoobank.org:act:B92BDB94-6E50-4429-83FC-611BA6C8C70F